2020
DOI: 10.1002/hyp.13706
|View full text |Cite
|
Sign up to set email alerts
|

Riparian canopy openings on mountain streams: Landscape controls upon temperature increases within openings and cooling downstream

Abstract: How much stream temperatures increase within riparian canopy openings and whether stream temperatures cool downstream of these openings both have important policy implications. Past studies of stream cooling downstream of riparian openings have found mixed results including rapid, slow, and no cooling. We collected longitudinal profiles of stream temperatures above, within, and below riparian forest openings along stream segments within otherwise forested riparian conditions to evaluate how sensi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…The higher the excess temperature of the incoming water compared to the equilibrium conditions in a river section, the higher the cooling effect. This is consistent with the modelling results of Davis et al (2016) and empirical data reported in Coats and Jackson (2020), where the cooling in a downstream shaded reach increased with water temperature in the upstream unshaded reach. It is reasonable that T range at the upstream start of the study sections increased with direct solar radiation input upstream, i.e.…”
Section: Woody Buffer Width and The Effect Of Narrow Bufferssupporting
confidence: 92%
See 1 more Smart Citation
“…The higher the excess temperature of the incoming water compared to the equilibrium conditions in a river section, the higher the cooling effect. This is consistent with the modelling results of Davis et al (2016) and empirical data reported in Coats and Jackson (2020), where the cooling in a downstream shaded reach increased with water temperature in the upstream unshaded reach. It is reasonable that T range at the upstream start of the study sections increased with direct solar radiation input upstream, i.e.…”
Section: Woody Buffer Width and The Effect Of Narrow Bufferssupporting
confidence: 92%
“…The principles how daily water temperature fluctuations and rates of warming and cooling caused by canopy cover decrease with stream size are well established. However, so far studies have mainly focused on small streams where the largest effects can be expected and studies comparing different stream sizes or types are rare: The empirical data reported in Coats and Jackson (2020) clearly indicated that the effect of canopy cover on water temperature decreases with catchment size. The modelled effect of 60% canopy cover on daily maximum water temperature was about −3.5°C in small headwater streams (Loicq et al, 2018, which is surprisingly similar to the −3.1°C predicted by our empirical equations for 0 oktas in May) and decreased to −1°C in the lower part of the catchment about 300 km from the source.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that limiting the spatial exposure to the stream channel by reducing the extent of treatments (treating shorter reaches of stream) may be an effective strategy to minimize local and downstream temperature changes. For example, recent studies have shown smaller temperature responses with v www.esajournals.org small-scale riparian gaps <30 m in length (Coats andJackson 2020, Swartz et al 2020). Third, we observed the emergence of distinct waveforms depending on the spatial proximity of thinning treatments.…”
Section: Management Implicationsmentioning
confidence: 99%
“…As a result, geomorphic and hydrologic conditions inherent in the system may influence responses that contribute to the context dependency observed among studies. Consideration of such conditions (e.g., underlying lithology, geomorphology, hydrology, watershed attributes, reach-scale attributes, and climate) provide ecological context to better understand responses to change (Moore et al 2005, Burnett et al 2007, Leach et al 2017, Bladon et al 2018, Coats and Jackson 2020.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Urban subwatersheds with more riparian canopy (Sweeney & Newbold, 2014) and less impervious area (Somers et al, 2013) will have cooler stream temperatures. Moving downstream, sites with more riparian canopy will have cooler temperatures (Coats & Jackson, 2020).…”
mentioning
confidence: 99%